Mthfs is an Essential Gene in Mice and a Component of the Purinosome - Field, Martha S.; Anderson, Donald D.; Stover, Patrick J. (Frontiers in Genetics, 2011)
Tetrahydrofolates (THF) are a family of cofactors that function as one-carbon donors in folate-dependent one-carbon metabolism, a metabolic network required for the de novo synthesis of purines, thymidylate, and for the remethylation of homocysteine to methionine in the cytoplasm. 5-FormylTHF is not a cofactor in one-carbon metabolism, but serves as a storage form of tetrahydrofolate cofactors. 5-formylTHF is mobilized back into the THF cofactor pool by methenyltetrahydrofolate synthetase (MTHFS), which catalyzes the irreversible and ATP-dependent conversion 5-formyltetrahydrofolate to 5,10-methenyltetrahydrofolate. Mthfs is not an essential gene in Arabidopsis, but MTHFS expression is elevated in animal tumors, enhances de novo purine synthesis, confers partial resistance to antifolate purine synthesis inhibitors and increases rates of folate catabolism in mammalian cell cultures. However, the mechanisms underlying these effects of MTHFS expression have yet to be established. The purpose of this study was to investigate the role and essentiality of MTHFS in mice. Mthfs was disrupted through the insertion of a gene trap vector between exons 1 and 2. Mthfsgt/+ mice were fertile and viable. No Mthfsgt/gt embryos were recovered from Mthfsgt/+ intercrosses, indicating Mthfs is an essential gene in mice. Tissue MTHFS protein levels are decreased in both Mthfsgt/+ and Mthfs+/+ mice placed on a folate and choline deficient diet, and mouse embryonic fibroblasts from Mthfsgt/+ embryos exhibit decreased capacity for de novo purine synthesis without impairment in de novo thymidylate synthesis. MTHFS was shown to co-localize with two enzymes of the de novo purine synthesis pathway in HeLa cells in a cell cycle-dependent manner, and to be modified by the small ubiquitin-like modifier (SUMO) protein. Mutation of the consensus SUMO modification sites on MTHFS eliminated co-localization of MTHFS with the de novo purine biosynthesis pathway under purine-deficient condit